2021
DOI: 10.1051/ro/2019066
|View full text |Cite
|
Sign up to set email alerts
|

Information sharing and leakage in the two-echelon supply chain

Abstract: We consider ex post demand information sharing and leakage in a two-echelon supply chain consisting of one supplier and two retailers competing in quantities. The incumbent retailer has an advantage to acquire information about the market at a cost. If he invests in information acquisition, he privately acquires a signal about the market demand. We examine the incumbent’s incentive of information acquisition and sharing, and the upstream supplier’s information leakage strategy. We confirm that the incumbent’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…They found that the supplier will always leak the demand information acquired from the incumbent retailer to the entrant retailer actively. Wang et al [29] extended the model of Anand and Goyal [1] by considering imperfect downstream competition and informationacquisition cost. Fang and Ren [6] further studied the strategic information management in a dual-channel supply chain consisting of one supplier and one retailer with information leakage and distortion.…”
mentioning
confidence: 99%
“…They found that the supplier will always leak the demand information acquired from the incumbent retailer to the entrant retailer actively. Wang et al [29] extended the model of Anand and Goyal [1] by considering imperfect downstream competition and informationacquisition cost. Fang and Ren [6] further studied the strategic information management in a dual-channel supply chain consisting of one supplier and one retailer with information leakage and distortion.…”
mentioning
confidence: 99%